The handbook of counseling - Locke, Don C.; Myers, Jane E.; Herr, Edwin L. (Counseling and psychotherapy transcripts, client narratives, and reference works., 2001)
A landmark publication in its field, The Handbook of Counseling is the authoritative voice of the counseling profession. Comprehensive in its scope, this text explores how the field has developed, the current state of the discipline, and where this dynamic profession is going.